TAHLÎL MULÂIMAH BUNÛD IKHTIBÂR AL-LUGHAH AL-‘ARABIYYAH AL-NIHÂÎ AL-WATHANÎ LI MANHAJ MUSTAWÂ AL-WAHDAH AL-TA’LÎMIYYAH (KTSP) WA TASHNÎF BLOOM AL-MU’ADDAL - Bahruddin, Uril; Qodri, Muhammad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This study aims to describe the suitability of Arabic language question item with educational unit level curriculum (KTSP) and Bloom’s taxonomy at the Final National Standard Madrasah (UAMBN) at Senior High School. This study used a qualitative approach with a descriptive type. Data was collected from exam documents on 2009/2010 and analysed using Krippendorff’s theory of content analysis . The findings of this study are (1) question items of Arabic language test of UAMBN academic year 2011/2012 for Senior High School level is suitable with Education Unit Level Curriculum in which the question items include: a) language element, and language skill (question items of reading and writing skills) that suitable with standard competency and basic competency. However, those question items are not including question items of phonetic and question items of listening and speaking skills. b) the suitable theme represented in each Standard Competency and Basic Competency from the first grade to third grade. (2) there is a correspondence between items of question that have met LOTS, MOTS and some HOTS.